Epistemological beliefs of secondary school students: relation goal orientations, learning approaches, and science achievement - Hutagalung, F.; Lee, W.S.; Simin, H.; Peng, C.F.; Noor Aishah, R. (2018)
The present study was conducted to examine the mediational role of achievement goal orientations and learning approach on the relation between epistemological beliefs about science and students' science achievement. This study was carried in the form of a survey, using questionnaires as a method of data collection. A total of 302 students (168 males, 134 females) between the age of 15-16 years old in Pahang, Malaysia participated in the study. Structure Equation Mode (SEM) was used to validate the proposed model. The result showed that epistemology beliefs exert a significant direct effect on science achievement. Mastery goals mediated the relationship between source and science achievement. Mastery, performance, and avoidance goals also mediated the relationship between certain and science achievement significantly. Mastery and avoidance goals mediated the relationship between development and science achievement. For the mediation role of learning approach, deep approach mediated the relationship between source and science achievement and also mediated the relationship between justification and science achievement. The result also showed that there are no significant differences.